Research status and trends of drug-coated balloons in coronary artery disease: a bibliometric analysis - Yu, Yue; Jiao, Yuemiao; Wang, Lüya; Zhang, Ming; Yin, Chengqian (Frontiers in Medicine, 2025)
ObjectiveDrug-coated balloons have emerged as a pivotal alternative to drug-eluting stents in the interventional management of coronary artery disease, particularly showing clinical advantages in the treatment of in-stent restenosis and small-vessel disease. This study provides a systematic bibliometric analysis of publication trends, research hotspots, and future directions in DCB-related CAD research from 2004 to June 2025.MethodsA total of 1,092 publications indexed in the Web of Science, Scopus, and PubMed databases were analyzed using CiteSpace, VOSviewer, and bibliometrix. Inclusion criteria were English-language papers, while case reports, conference proceedings, news articles, and duplicate publications were excluded. The analysis focused on publication trends, country/institutional contributions, author collaboration networks, journal analysis, co-citation literature, and keyword evolution.ResultsThree distinct developmental phases of DCB research were identified: (1) device optimization (2004–2010), (2) clinical validation (2010–2017), and (3) application to complex lesions (2018–present). China led in publication volume (n = 180), while Germany and Italy demonstrated the highest research impact. Leading research institutions included Capital Medical University and Friedrich Schiller University of Jena. High-impact journals such as JACC: Cardiovascular Interventions and EuroIntervention served as key publication venues, with a focus on clinical outcomes and intravascular imaging. Keyword analysis revealed a growing emphasis on intravascular imaging modalities and emerging drug-coating technologies in recent research.ConclusionDCB are now established as a standard of care for ISR (Class IA recommendation), with accumulating evidence supporting their efficacy and safety in small-vessel coronary disease. However, their application in complex lesions requires further validation through multicenter randomized controlled trials. Future research should focus on optimizing drug coating technologies, refining imaging-guided strategies, exploring new anti-proliferative drugs, and establishing more precise eligibility criteria for treatment.